THE INFLUENCES OF GOOD CORPORATE GOVERNANCE AND PROFITABILITY ON EARNINGS MANAGEMENT AT COMMERCIAL BANKS BY PANEL DATA REGRESSION ANALYSIS - Ladini, Urwawuska; Nengsih, Titin Agustin; Wulandari, Wulandari; Anggraeni, Lidya (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 8 No 1 (2022): The 8th International Conference Of Islamic Economics And Business (ICONIES 2022), 2022)
The company's financial statements are needed by external parties in assessing performance to obtain information related to the financial condition of a company. This financial report is processed by the management team in order to carry out earnings management to be shown to external parties by increasing or decreasing profits in order to get a good impression and obtain personal benefits. This study will be examined the effect of Good Corporate Governance (GCG) and profitability (ROA and ROE) on earnings management (discretionary accruals) from data of 16 commercial sharia and conventional banking companies in Indonesia from 2016-2020 using panel data regression analysis. The results showed that simultaneously, 11.28% of earnings management being influenced by GCG, ROA, and ROE. Only the ROA and ROE variables had a significant impact on earnings management. Based on this discussion, recommendations for further research are to add more other variables to see their effect on earnings management and compare the results when applied using other methods.